Deconvolution of single-cell multi-omics layers reveals regulatory heterogeneity - Liu, Longqi; Quintero, Andrés; Herrmann, Carl; Eils, Roland (Nature Communications, 2019)
Heterogeneity in gene expression and epigenetic states exists across individual cells. Here, the authors develop scCAT-seq, a technique for simultaneously performing ATAC-seq and RNA-seq within the same single cell.